Comparative Study of Surface Modification Treatment for Porous Titanium - Reiko Kobatake; Kazuya Doi; Yoshifumi Oki; Yusuke Makihara; Hanako Umehara; Takayasu Kubo; Kazuhiro Tsuga (Stilus Optimus, 2020)
Objectives: This study was to investigate suitable surface treatment methods for porous titanium by ex vivo study of material properties and calcium phosphate deposition in simulated body fluid. Material and Methods: Porous titanium with acid (H2SO4 and HCl mixed acid) or alkali (NaOH) treatment was prepared. The surfaces were observed, and the weight change ratio (after and before surface treatment) and compression strength were measured. To investigate the apatite formation ability, each sample was immersed in simulated body fluid (SBF). Surface observations were performed, and the weight change ratio (before/after immersing SBF) and calcification (by alizarin red staining) were measured. Results: The acid group showed a martensitic micro-scale rough structure and the weight and mechanical strength greatly decreased compared to the other groups. The alkali group exhibited a nano-scale roughness structure with similar weight and mechanical strength. Following immersion in SBF, an apatite-like crystal layer in the alkali group was observed. The weight of all samples increased. The change in weight of the samples in the alkali, acid, and control groups were significantly different, showing the following trend: alkali group (1.6%) > acid group (1.2%) > control group (0.8%). Calcium precipitation values were higher in the samples from alkali group than in those from the acid and control groups. Conclusions: Alkali treatment was found to be a suitable surface modification method for porous titanium, resulting in good mechanical strength and apatite formation ability in simulated body fluid.